Puzzle Design for Enhancing Bible Story Learning for Children 4-6 Years Old - Merielle, Carrolina Thessalonica; Bahri, Nurul Fitriana; Nurhidayat, Martiyadi (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
In the contemporary era characterized by novel distractions and challenges, we frequently observe the diminished comprehension of biblical narratives within religious education settings, including St. Gabriel Sunday School. Despite ongoing efforts to convey religious messages in a creative and captivating manner, numerous children encounter difficulties in comprehending and internalizing the moral teachings encapsulated within the scriptures. This presents a pertinent inquiry regarding the most effective strategies to engage the younger generation with religious messages in this rapidly evolving and intricate global environment. The primary objective of this research is to design an educational puzzle as a medium for acquiring biblical narratives for children aged 4 to 6 years. Utilizing the SCAMPER (Substitute, Combine, Adapt, Modify, Put to another use, Eliminate, and Reverse) design methodology, this research identifies and develops puzzles that are engaging and facilitate children’s comprehension of biblical narratives. The puzzle is meticulously crafted to enhance children’s engagement and proficiency through an interactive and enjoyable learning experience. The anticipated outcomes of this research include the development of an effective and engaging educational puzzle tailored for children aged 4 to 6 years, thereby supporting their biblical knowledge and overall development.